Environmental fate of hydraulic fracturing fluid additives after spillage on agricultural topsoil - McLaughlin, Molly C., author; Blotevogel, Jens, advisor; Borch, Thomas, advisor; DiVerdi, Joseph, committee member (Colorado State University. Libraries, 2016)
Inadvertent releases of hydraulic fracturing fluid may occur at many different stages, with surface spills being the most commonly reported cause of contamination. Hydraulic fracturing (HF) frequently occurs on agricultural land, where surface spills have the potential to impact soil, groundwater and surface water quality. However, the extent of sorption, transformation, and interactions among the numerous organic HF fluid and oil & gas wastewater constituents upon environmental release is hardly known. Thus, this study aims to advance our current understanding of processes that control the environmental fate and toxicity of commonly used hydraulic fracturing chemicals with a specific focus on co-contaminant effects. Hydraulic fracturing fluid releases were simulated using aerobic batch studies conducted with a topsoil collected from Weld County, Colorado, an area where reservoirs are frequently stimulated. Each batch reactor contained varying combinations of the biocide glutaraldehyde (GA), polyethylene glycol (PEG) surfactants, and a polyacrylamide (PAM)-based friction reducer, three widely used hydraulic fracturing fluid components. Furthermore, the presence of salt was investigated in the experiments, often present at high concentration in produced water from hydraulic fracturing operations. Results showed that aqueous GA concentrations decreased by as much as 40% in the first three days of the experiment as a result of sorption to soil. Complete biodegradation of this biocide occurred in all reactors in 33 to 57 days, with the slowest removal occurring in the reactor containing salt. The fastest removal of GA was observed in the reactors containing PAM friction reducer, where degradation rates increased by 50% as compared to reactors without PAM. This increase in removal is attributed to the cross-linking reaction between GA and primary amine functional groups in the friction reducer. In the absence of GA and salt, PEG surfactants were completely biodegraded in agricultural topsoil within 42 to 71 days. Their transformation was impeded, however, in the presence of the biocide GA, and completely inhibited in the presence of 30 g/L sodium chloride, a concentration in the typical range for oil and gas wastewater. No aqueous removal of PAM was observed over a period of six months. However, adenosine triphosphate (ATP) concentrations were consistently higher in reactors containing PAM friction reducer, suggesting this additive supplied an easily accessible source of nitrogen to the microbial soil community. The findings of this study highlight the necessity to consider co-contaminant effects when we evaluate the risk of frac fluid additives and oil and gas wastewater constituents in agricultural soils in order to fully understand their human health impacts, likelihood for crop uptake, and potential for groundwater contamination.
Keywords: friction reducer; hydraulic fracturing; surfactant; glutaraldehyde; biocide; polyethylene glycol